Respuesta :

Answer:

1/3

Step-by-step explanation:

5/6 - 1/2

note that you could also write 1/2 as 3/6 since when divided you get half once again .

5/6- 3/6 = (5-3)/6= 2/6 = 1/3

Answer:

The answer is

[tex] \huge \frac{1}{3} [/tex]

Step-by-step explanation:

[tex] \frac{5}{6} - \frac{1}{2} \\ [/tex]

To solve this first find the common denominator

From the question the common denominator is 6

So we have

[tex] \frac{5}{6} - \frac{1}{2} = \frac{5 - 3}{6} = \frac{2}{6} = \frac{1}{3} \\ [/tex]

We have the final answer as

[tex] \frac{1}{3} \\ [/tex]

Hope this helps you